Personal and In-store Factors Influencing Impulse Buying Behavior among Generation Y Consumers of Small Cities. Issue 1 (January 2019) - Husnain, Mudassir; Rehman, Bushra; Syed, Fauzia; Akhtar, Muhammad Waheed
Abstract: For decades, impulse buying is considered to be one of the significant factors to increase sales volume in the retail sector. Past studies have investigated the impulsive buying behavior of generation Y consumers in retail settings of somewhat medium- and large-sized cities. Therefore, how certain situational or in-store factors can propagate impulse buying in the retail settings of small cities has been widely ignored. This article explores the influence of situational variables categorized as personal factors (time availability, family influence, money availability) and in-store factors (store environment, sales promotions, and friendly store employees) on generation Y impulse buying behavior in the Pakistani context in general and the country's small cities in particular. A self-administered survey was used to elicit information from 422 purposively selected respondents (living in various cities of Punjab, Pakistan). Data have been analyzed by using Statistical Package For Social Science (SPSS) and Analysis of Moment Structure (AMOS) for structural equation modeling (SEM). Results revealed that personal factors, that is, time availability and family influence has significant and positive impact on the impulse buying behavior of generation Y consumers in Pakistan, also in-store factors except money availability has significant impact on impulse buying behavior. Recommendations for retail management have been given at the end of the article.